(untitled) (Swiss Medical Weekly, 2015)
Approximately 3% of the world population is estimated to have a chronic hepatitis C virus (HCV) infection and 500,000 individuals die from its consequences yearly. Persons who inject drugs (PWID) bear the majority of the disease burden in high-income countries. Drug substitution programmes have helped reduce HCV transmissions among PWID. However, recent epidemics of sexually transmitted HCV infections in HIV-infected men who have sex with men demonstrated the changing nature of the HCV epidemic. HCV therapy is undergoing a revolution, as new interferon-free, oral treatments eradicate HCV infections in almost all treated patients. As a consequence, the eradication of HCV has become a matter of debate and is becoming an important future public health target. However, for this to be achieved, many challenges need to be addressed, including the poor uptake of HCV testing, the high cost of the new antiviral combinations and the high frequency of re-infections after treatment in some populations.